Local allergic reaction in the conjunctiva – therapeutic implications - Bogacka, Ewa; Groblewska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The eye is exposed to many foreign substances, and ocular tissues have a complete array of immune cells to initiate an immunological response. The external eye represents an ideal site for allergic reactions because of the high number of mast cells and potential local synthesis of IgE. Mild allergic diseases such as IAC and PAC are classical example of type I hypersensitivity. The central mechanism in the pathogenesis of these diseases is IgE-mediated reactions and then T lymphocytes, eosinophils and conjunctival structural cells activation. But the severest forms of ocular allergy are more complicated and involve a cellular, neurogenic and hormonal response. Knowledge about these differences between different kinds of allergic eye diseases is necessary to decide about appropriate therapy. The pharmacotherapy of eye allergy consists of successive classes of drugs: antihistamines, mast cell stabilizers, dual-acting antihistamines, NSAIDs, corticosteroids, immunomodulators and immunotherapy.